Crystal structure and Hirshfeld surface analysis of (2E,20E)-3,30-(1,4-phenylene)bis[1-(2,4-difluorophenyl) prop-2-en-1-one] - Huey, Chong Kwong; Aijia, Sim; C. S., Chidan Kumar; Li, Yee Then; Win, Yip Foo; Ching, Kheng Quah; S., Naveen; Warad, Ismail (International Union of Crystallography, 2017)
The asymmetric unit of the title compound, C24H14F4O2, comprises of one and a half molecules; the half-molecule is completed by crystallographic inversion symmetry. In the crystal, molecules are linked into a three-dimensional network by C—H F and C—H O hydrogen bonds. Some of the C—H F links are unusually short (< 2.20 A ° ). Hirshfeld surface analyses (dnorm surfaces and twodimensional fingerprint plots) for the title compound are presented and discussed.